2010
DOI: 10.5507/bp.2010.011
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rhythm and Atrial Transport Function After Surgical Ablation of Atrial Fibrillation Using Cryoenergy: Predictors and Effectiveness of the Procedure

Abstract: Aim. The aim of this prospective study was to assess the presence of sinus rhythm and atrial transport function after surgical ablation of atrial fibrillation using cryoenergy, and to evaluate predictors of the success of the procedure.Methods. Between January 2005 and September 2006, 100 consecutive patients underwent left atrial cryoablation as a concomitant surgical procedure (46 patients with paroxysmal or persistent atrial fibrillation and 54 with permanent atrial fibrillation). Mitral valve surgery was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
1
7
0
1
Order By: Relevance
“…In our present, as well as previous study [ 58 ], we managed to achieve similar good outcomes with performance of left atrium ablation in achievement and duration of NSR in the group of patients with paroxysmal and persistent AF. However, in the group of patients with long-standing persistent, or permanent AF, we observed a significantly higher AF recurrence, which increases with the period of follow-up.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our present, as well as previous study [ 58 ], we managed to achieve similar good outcomes with performance of left atrium ablation in achievement and duration of NSR in the group of patients with paroxysmal and persistent AF. However, in the group of patients with long-standing persistent, or permanent AF, we observed a significantly higher AF recurrence, which increases with the period of follow-up.…”
Section: Discussionsupporting
confidence: 81%
“…2.2% at the end of one-year follow-up. In the previous study [ 58 ] performed at our centre, the incidence of thromboembolic events was 4.6%, or 5.9%, at the end of one-year and two-year follow-up, respectively. This corresponds with the frequency of thromboembolic events in patients after surgical ablation presented in published studies and results summarized in the meta-analysis by Gray et al from 2011 [ 74 ].…”
Section: Discussionmentioning
confidence: 91%
“…At five-year follow-up it was shown that those who had undergone cryoablation had a higher (although non-significant) rate of SR conversion compared with the microwave group (79.9% vs. 61.3%, P=0.089). Given that aortic cross-clamp time was longer in the cryoablative group and the fact that there were no significant Kolek and Brat [8] and Mack et al [9] reviewed the results of left atrial cryoablation. In agreement with Gammie et al [7], Kolek and Brat showed a high rate of SR conversion in those suffering paroxysmal but not permanent AF after 12-month follow-up (89.7 vs. 61.9%, P=0.005).…”
Section: Resultsmentioning
confidence: 99%
“…All nine papers were either small randomised controlled trials or retrospective studies with small sample sizes (57-521) and varied follow-up regimens. Six of nine studies [2,[4][5][6][7][8] suggested that cryoablation is most successful in patients suffering from paroxysmal rather than permanent AF. A lack of 24-hour monitoring in seven of nine studies [2-6, 9, 10] prevents effective elucidation of the rate of paroxysmal AF following cryoablation.…”
Section: Clinical Bottom Linementioning
confidence: 98%
“…Rovněž platí, že obnova SR ne vždy znamená obnovu mechanické (transportní) funkce síní. Podle literárních údajů je účinná transportní funkce levé síně obnovena u 60-90 % a účinné kontrakce pravé síně u 80-100 % pacientů s úspěšně obnoveným SR [52]. Prav-děpodobnost obnovy transportní funkce levé síně roste spolu s dobou uplynulou od zákroku; proto období pooperačního "omráčení" síně i pacienti, u nichž k obnově transportní funkce nedojde vůbec, představují jedince spojené s vyšším tromboembolickým rizikem i v přítomnosti SR. Zde pomáhá před případným vysazením antikoagulace echokardiografi cké vyšetření, které je cílené na transportní funkci síní.…”
Section: Diskuseunclassified